Exploration and collecting expedition on the Cheradi islands (southern Italy), 2004 - Laghetti, G.=700 1 Sonnante, G.; Cifarelli, S.; Hammer, K.
(Es,Fr,En)
ilus., 11 ref.
Keywords: RECURSOS GENETICOS; CONSERVACION DE LOS RECURSOS; RECOLECCION; GRANOS; ITALIA